2011
DOI: 10.1103/physrevb.84.205120
|View full text |Cite
|
Sign up to set email alerts
|

Phase separation and charge-ordered phases of thed=3Falicov-Kimball model at nonzero temperature: Temperature-density-chemical potential global phase diagram from renormalization-group theory

Abstract: The global phase diagram of the spinless Falicov-Kimball model in d = 3 spatial dimensions is obtained by renormalization-group theory. This global phase diagram exhibits five distinct phases. Four of these phases are charge-ordered (CO) phases, in which the system forms two sublattices with different electron densities. The CO phases occur at and near half filling of the conduction electrons for the entire range of localized electron densities. The phase boundaries are second order, except for the intermediat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…Hubbard model [13][14][15][16], t -J model [17][18][19][20] and Falicov-Kimball model [21]. For the XXZ model, although this approach works best at high temperatures in Ising limits ( T ≫T , |∆| ≫ 1), previously we demonstrated that even in the opposite zero-temperature XY limit ( T = 0 , ∆ = 0 ), ST RG results obtained for d = 1 and d = 2 , compare well with other approximate results, or with exact results if available.…”
Section: Methodsmentioning
confidence: 99%
“…Hubbard model [13][14][15][16], t -J model [17][18][19][20] and Falicov-Kimball model [21]. For the XXZ model, although this approach works best at high temperatures in Ising limits ( T ≫T , |∆| ≫ 1), previously we demonstrated that even in the opposite zero-temperature XY limit ( T = 0 , ∆ = 0 ), ST RG results obtained for d = 1 and d = 2 , compare well with other approximate results, or with exact results if available.…”
Section: Methodsmentioning
confidence: 99%